7
$\begingroup$

Compute this limit of series:

$\displaystyle \lim_{n\rightarrow \infty} \frac{1}{n^{3}}\sum_{k=1}^{n-1}k^2 $

I used the definition of the definite integral

$\displaystyle \int_{a}^{b}f(x)dx=\lim_{n\rightarrow \infty} S_{n}$

where $\displaystyle f(x)=x^2$, $\displaystyle [a,b]=[0,1]$; since the function is continuous in $\displaystyle [0, 1]$ then it is certainly integrated.

$\displaystyle \int_{0}^{1}x^2dx=\lim_{n\rightarrow \infty} \sum_{k=1}^{n-1}\frac{1}{n}\ \left(\frac{k}{n}\right)^2=\lim_{n\rightarrow \infty} \frac{1}{n^3}\sum_{k=1}^{n-1}k^2$

We have:

$\displaystyle\int_{0}^{1}x^2dx=\frac{1}{3}$

then

$\displaystyle \lim_{n\rightarrow \infty} \frac{1}{n^{3}}\sum_{k=1}^{n-1}k^2 =\frac{1}{3}$

Any suggestions, please? This limit can be solved in other ways?

Thanks.

$\endgroup$
6
$\begingroup$

By induction, you can prove that

$\displaystyle \sum_{k = 1}^n k^2 = \frac{n(n + 1)(2n + 1)}{6}$

Thus

$\displaystyle \lim_{n \rightarrow \infty}\frac{1}{n^3}\sum_{k = 1}^{n - 1} k^2 = \lim_{n \rightarrow \infty}\frac{1}{n^3}\frac{(n - 1)(n)(2(n - 1) + 1)}{6} = \lim_{n \rightarrow \infty}\frac{1}{n^3}\frac{(n - 1)(n)(2n - 1)}{6} = \lim_{n \rightarrow \infty}\frac{2n^3 - 3n^2 + n}{6n^3}$

$\displaystyle \lim_{n \rightarrow \infty}\frac{1}{3} - \frac{1}{2n} + \frac{1}{6n^2} = \frac{1}{3}$

$\endgroup$
5
$\begingroup$

Well done. The Riemann sum argument was carried out efficiently.

For another way of solving the problem, we can use the fact that the sum $\sum_{k=1}^n k^2$ is given by the explicit formula $$\sum_{k=1}^n k^2=\frac{n(n+1)(2n+1)}{6}.$$
I have quoted the sum to $n$, because it is the standard version, but you can get the explicit formula for the sum to $n-1$ by making the obvious substitution.

There are many ways to prove the above formula. One way is by induction.

So (after the substitution) we want to find the limit of $$\frac{(n-1)(n)(2n-1)}{6n^3}.$$ Cancel an $n$, then divide top and bottom by $n^2$. We want $$\lim_{n\to\infty}\frac{\left(1-\frac{1}{n}\right)\left(2-\frac{1}{n}\right)}{6}.$$

Remark: For additional explicit "sums of powers" formulas, please see the Wikipedia article on Faulhaber's Formula.

$\endgroup$
3
$\begingroup$

What you have is fine. If one knows the formula $\sum_{k=1}^nk^2=\frac16n(n+1)(2n+1)$, one can avoid the integration:

$$\sum_{k=1}^{n-1}k^2=\frac16n(n-1)(2n-1)=\frac{2n^3-3n^2+n}6\;,$$

so $$\lim_{n\rightarrow \infty} \frac{1}{n^{3}}\sum_{k=1}^{n-1}k^2=\lim_{n\to\infty}\frac{2-\frac3n+\frac1n}6=\frac13\;.$$

$\endgroup$
2
$\begingroup$

where $\displaystyle f(x)=x^2$, $\displaystyle [a,b]=[0,1]$; since the function is continuous in $\displaystyle [0, 1]$ then it is certainly integrated.

$\displaystyle \int_{0}^{1}x^2dx=\lim_{n\rightarrow \infty} \sum_{k=1}^{n-1}\frac{1}{n}\ \left(\frac{k}{n}\right)^2=\lim_{n\rightarrow \infty} \frac{1}{n^3}\sum_{k=1}^{n-1}k^2$

We have:

$\displaystyle\int_{0}^{1}x^2dx=\frac{1}{3}$

then

$\displaystyle \lim_{n\rightarrow \infty} \frac{1}{n^{3}}\sum_{k=1}^{n-1}k^2 =\frac{1}{3}$

$\endgroup$
0
$\begingroup$

Also, if you know it, this is a straightforward application of Stoltz-Cezaro:

$$\lim_{n\rightarrow \infty} \frac{1}{n^{3}}\sum_{k=1}^{n-1}k^2=\lim_{n\rightarrow \infty} \frac{\sum_{k=1}^{n}k^2-\sum_{k=1}^{n-1}k^2}{(n+1)^{3}-n^3}= \lim_{n\rightarrow \infty} \frac{n^2}{3n^2+3n+1}=\frac{1}{3}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.